2017
DOI: 10.1108/mhrj-01-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Measurement issues of shared decision making in mental health: challenges and opportunities

Abstract: Purpose Shared decision making (SDM) is a model of health care in which patients are involved in the decision-making process about their treatment, considering their preferences and concerns in a deliberative process with the health care provider. Many existing instruments assess the antecedents, process, or the outcomes of SDM. The purpose of this paper is to identify the SDM-related measures applied in a mental health context. Design/methodology/approach The authors performed a systematic review in several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 118 publications
0
18
0
Order By: Relevance
“…the deliberation behaviour of health professionals) or decision outcomes (e.g. satisfaction with the decision) (Perestelo-Perez et al, 2017).…”
Section: Choosing Clinical Decision-making Involvement and Satisfacmentioning
confidence: 99%
“…the deliberation behaviour of health professionals) or decision outcomes (e.g. satisfaction with the decision) (Perestelo-Perez et al, 2017).…”
Section: Choosing Clinical Decision-making Involvement and Satisfacmentioning
confidence: 99%
“…Several different instruments have been developed to assess the complex and multifaceted phenomenon of shared decision-making in the healthcare setting ( Bouniols et al ., 2016 ; Makoul & Clayman, 2006 ; Scholl et al ., 2011 ; Simon et al ., 2007 ). These scales measure different components or phases in the SDM process between physicians and patients having cognitive capacity, such as antecedents of the decision-making process, the process itself and the decision outcomes ( Perestelo-Perez et al ., 2017 ; Scholl et al ., 2011 ).…”
Section: Shared Decision-making and Its Recent Developmentmentioning
confidence: 99%
“…(2016) , highlighting the evolution of instruments which take into account points of view of patients, HCPs and external observers. Recently, Perestelo-Perez et al (2017) focused on SDM measures within the mental health area and reported 48 instruments, mainly assessing the SDM process from the patients’ perspective.…”
Section: Shared Decision-making and Its Recent Developmentmentioning
confidence: 99%
“…Reflection on SDM training for service users, care-coordinators and psychiatrists given by O'sullivan and Rae in the paper on implementation of SDM helps to understand better what each group looks for in SDM and in training for it. Evaluation of both SDM measures in mental health is essential to enable SDM to meet the promise of improving communication and mutual learning (Perestelo-Perez et al, 2017) Key issues that require clarification in the context of SDM include what are effective processes of sharing such different types of knowledge between service users and providers who have unequal power positions in our respective societies? What are the necessary and sufficient conditions for a trusting and respectful relationships between these key stakeholders and relevant others (such as family members)?…”
Section: Shared Decision Making In Mental Health: Special Issue Of Thmentioning
confidence: 99%
“…, the range of SDM interventions and their underlying components (Zisman-Ilani et al, 2017), SDM from the perspective of recovery-oriented person centred care (Davidson et al, this issue), SDM measures and outcomes(Perestelo-Perez et al, 2017), and the implementation of SDM in everyday practice(Ramon et al, 2017), of which relatively little has been published up to now.…”
mentioning
confidence: 99%